PENERAPAN MEDIA E-LEARNING BERBASIS MOODLE UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM PEREDARAN DARAH MANUSIA - Tawaffani Muslimah; An Nuril Maulida Fauziah (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2021)
This study aims to describe the implementation of learning, increase student learning outcomes and student responses during the learning process usingmedia -e-learning based Moodle on the human blood circulatory system material. This study used a One Group Pretest-Posttest Design. This research was conducted on 34 students of SMP Satu Atap Pengampon class VIII. The instruments used were in the form of a learning implementation sheet, a test question sheet, and a student response questionnaire. The data collection techniques in this study were observation techniques, test techniques, and questionnaire techniques. The data analysis used was the analysis of the implementation of learning, the analysis of the assessment of knowledge, and the analysis of the student response questionnaires. The results of this study are in the form of learning implementation, learning outcomes, and student responses. The implementation of learning in class VIII has a very good category, with an average value of the learning process of 3.8. The student learning outcomes that are assessed are in the knowledge aspect obtained from the average N-Gain test score of 0.70 which is included in the high criteria. Student learning outcomes are known from the students' pretest and posttest scores. Student posttest results have increased after the implementation ofmedia -e-learning based Moodle on the human circulatory system material. Student responses during the learning process using Moodle-based e-learning media contained 12 questions (assessed aspects) with an average percentage value of the student's “Yes” answer of 89% with a very good category. The conclusion of this study is the application ofmedia -e-learning based Moodle on the human circulatory system material can improve junior high school student learning outcomes.